2022
DOI: 10.1136/jnis-2022-019365
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus migration in ischemic stroke due to large vessel occlusion: a question of time

Abstract: BackgroundThrombus migration (TM) is frequently observed in large vessel occlusion (LVO) ischemic stroke to be treated by endovascular thrombectomy (EVT). TM may impede complete recanalization and hereby worsen clinical outcomes. This study aimed to delineate factors associated with TM and clarify its impact on technical and functional outcome.MethodsAll patients undergoing EVT due to LVO in the anterior circulation at two tertiary stroke centers between October 2015 and December 2020 were included. Source ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Median age in the study population was 77 years (IQR 65-83) and 5365 patients (52.8%) were women. Median National Institutes of Health Stroke Scale score was 14 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The prevalences of occlusion of the carotid T, the proximal or distal M1 segment, and the M2 segment of the middle cerebral artery were 18.9%, 38.2%, 25.5%, and 27.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median age in the study population was 77 years (IQR 65-83) and 5365 patients (52.8%) were women. Median National Institutes of Health Stroke Scale score was 14 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The prevalences of occlusion of the carotid T, the proximal or distal M1 segment, and the M2 segment of the middle cerebral artery were 18.9%, 38.2%, 25.5%, and 27.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The idea to omit IVT was fueled by observations that proximal occlusions with long thrombi have a lower likelihood to recanalize with IVT alone, 5,6 higher rates of symptomatic intracranial hemorrhages in patients treated with IVT, 7 and the potential risks of thrombus migration and distal embolization, increasing EVT complexity. [8][9][10] Moreover, an early meta-analysis suggested that EVT alone may be non-inferior to EVT plus IVT. 11 This conclusion, however, was not based on stringent non-inferiority margins and only included data from the first three RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies reported improved outcomes in patients with pre-EVT arterial recanalization, 11,15 while others reported no differences. 10,12 In this study, we aimed to determine the incidence of recanalization during interhospital transfer for EVT, the clinical and imaging predictors of recanalization, and the relationship between recanalization and immediate posttransfer and 3-month clinical outcomes.…”
mentioning
confidence: 99%
“…Some of these studies reported improved outcomes in patients with pre-EVT arterial recanalization, 11,15 while others reported no differences. 10,12…”
mentioning
confidence: 99%
“…For instance, catheter aspiration is less effective for massive emboli occupying long distances, and stent retrieval may cause distal migration of the emboli when crossing the lesion, which deteriorates cerebral perfusion by blocking residual collateral flow. 4 , 5 …”
mentioning
confidence: 99%